Comprehensive approach to energy efficiency assessment of induction furnaces under unstable power supply - Zozulia, V.; Усенко, С. М. (Energy and Automation, 2025)
A comprehensive approach to evaluating the energy efficiency of induction furnaces under unstable power supply has been developed, integrating electromagnetic, thermodynamic, and stochastic models. The influence of power grid parameter fluctuations on electromagnetic field penetration depth, eddy current distribution, and temperature gradients in the melt has been investigated. The nonlinear nature of heating power dependence on voltage and frequency deviations has been established. A mathematical model for probabilistic assessment of energy losses under various types of power supply anomalies has been formulated. A methodology for calculating integral energy efficiency indicators has been developed, including the coefficient of variation of efficiency and the probability of ensuring a minimum acceptable efficiency level. A phenomenological analysis of the relationship between power quality indicators and thermodynamic characteristics of the melting process has been conducted. Theoretical principles for constructing adaptive control systems for induction furnaces based on predictive models of power grid fluctuations have been substantiated. The research results create a theoretical basis for developing intelligent control systems for induction melting units capable of ensuring an optimal balance between energy efficiency and product quality. Key words: induction furnace, energy efficiency, unstable power supply, electromagnetic field, stochastic modeling, adaptive control, metallurgical processes